Adverse Reactions from Topical Ophthalmic Anesthetic Abuse - Ali Sharifi; Naser Naisiri; Majid Shams; Meraj Sharifi; Hamid Sharifi (Journal of Ophthalmic & Vision Research, 2022)
Abstract Purpose: To assess the adverse drug reactions (ADR) of tetracaine among patients referred to an eye emergency department in the southeast of Iran. Methods: In this case series study, we assessed 31 eyes of 24 patients who were referred due to adverse effects of ocular anesthetics during2017–2020. We collected the data, including age, sex, job, how the medicine was obtained, symptoms, examination results, and ADR. Results: Of 24 patients, 22 (91.7%) were male. The mean (standard deviation) age of the patients was 32.6 (1.9) years. Twenty-two patients obtained the medicines without a prescription and a general practitioner prescribed the medicine to two patients. In the first interview, the most common symptoms were: photophobia, reduced vision, ocular pain, and redness. The main signs of persistent epithelial defect, patchy or diffuse corneal stromal infiltration, ring infiltration, and Descemet's folds were noticed in the examinations. Finally, 51.6% (n =16) of the eyes had decreased vision, 45.2% (n =14) had corneal opacity, 16.1% (n = 5) had elevated intraocular pressure that needed long-term anti-glaucoma therapy, and 6.5% (n = 2) had corneal pannus. Corneal perforation and phthisis bulbi were the final results in one eye. Conclusion: ADR related to the use of ophthalmic topical anesthetics could cause sight-threatening severe morbidities. It seems that some general practitioners are not careful regarding the prescription of these kinds of medicine. Moreover, the over-the-counter availability of tetracaine eye drops should be managed.